Neonatal neurological examination during the first 6 h after birth. (May 2017) - Romeo, Domenico M.; Bompard, Sarah; Cocca, Carmen; Serrao, Francesca; De Carolis, Maria Pia; Zuppa, Antonio A.; Ricci, Daniela; Gallini, Francesca; Maddaloni, Chiara; Romagnoli, Costantino; Mercuri, Eugenio
Abstract: Background: Few neurological assessments are easily performed during the first 6 h after birth. Aims: To assess a cohort of low risk term born newborns within the first 6 h and at 48 h after birth using the Hammersmith Neonatal Neurological Examination. Study design and subjects: A population of low risk term born newborns was examined within 3 h from birth or between 3 and 6 h. Each infant was re-assessed at 48 h, establishing the range and frequency distribution of neonatal neurological scores at each time point. Results: Of the 124 full-term born newborns, 62 were assessed at 0–3 h and 62 at 3–6 h. All infants were re-assessed at 48 h. For 23/34 of the neurological items, the range and median scores were similar across the 3 time points. In the remaining 11 items the three groups had a similar range of scores but the median scores were different with different rates of changes. In 6 of the 11 the median scores at 3–6 h were similar to those observed at 48 h but they appeared to be 'less mature' at 0–3 h. Only in one item the median scores were consistently different at the 3 time points. Conclusions: Our results suggest that a neurological examination can already be reliably performed soon after birth. These findings will help in the interpretation of the few items that show changes with increasing postnatal age. Highlights: This study provides information on the early neurological assessment of the newborn baby. A complete neurological examination can already be reliably performed soon after birth The neurological findings before and after 6 h after birth were similar.